2014
DOI: 10.1039/c4dt00047a
|View full text |Cite
|
Sign up to set email alerts
|

Redox and acid–base properties of asymmetric non-heme (hydr)oxo-bridged diiron complexes

Abstract: The diiron unit is commonly found as the active site in enzymes that catalyze important biological transformations. Two μ-(hydr)oxo-diiron(iii) complexes with the ligands 2,2'-(2-methyl-2-(pyridine-2-yl)propane-1,3-diyl)bis(azanediyl)bis(methylene)diphenol (H2L) and 2,2'-(2-methyl-2(pyridine-2-yl)propane-1,3-diyl)bis(azanediyl)bis(methylene)bis(4-nitrophenol) (H2L(NO2)), namely [(FeL)2(μ-O)] () and [(FeL(NO2))2(μ-OH)]ClO4 () were synthesized and characterized. In the solid state, both structures are asymmetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 65 publications
(101 reference statements)
1
18
0
Order By: Relevance
“…In Solomon's studies, enhanced basicity is observed with a more acute Fe–O–Fe angle due to a reduction in the Fe–O orbital overlap, thereby resulting in pronounced electron density on the bridging oxide ligand when examining an isovalent series 3,42. Further comparison with other diiron μ-oxo complexes corroborates this relationship, as a diiron( iii ) μ-oxo synthesized by Houser and coworkers10 (∠Fe–O–Fe 143.71(10)°, p K a 21.3(1)) is several orders of magnitude more basic than 6 (∠Fe–O–Fe 167.1(3)°, p K a –1.8(6)) (Table 1); whereas an example by Grapperhaus and coworkers43 with similar core metrics to 6 (∠Fe–O–Fe 168.47(13)°, p K a 6.1(3)) is less basic than the Houser example. The Grapperhaus example is more basic than 6 , which can be attributed to differences in coordination geometry; the tetrahedral iron sites in 6 are influenced more by the enhanced covalency to the oxo moiety (due to the increased iron electrophilicity) than the octahedrally coordinated iron sites in the Grapperhaus example 43…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…In Solomon's studies, enhanced basicity is observed with a more acute Fe–O–Fe angle due to a reduction in the Fe–O orbital overlap, thereby resulting in pronounced electron density on the bridging oxide ligand when examining an isovalent series 3,42. Further comparison with other diiron μ-oxo complexes corroborates this relationship, as a diiron( iii ) μ-oxo synthesized by Houser and coworkers10 (∠Fe–O–Fe 143.71(10)°, p K a 21.3(1)) is several orders of magnitude more basic than 6 (∠Fe–O–Fe 167.1(3)°, p K a –1.8(6)) (Table 1); whereas an example by Grapperhaus and coworkers43 with similar core metrics to 6 (∠Fe–O–Fe 168.47(13)°, p K a 6.1(3)) is less basic than the Houser example. The Grapperhaus example is more basic than 6 , which can be attributed to differences in coordination geometry; the tetrahedral iron sites in 6 are influenced more by the enhanced covalency to the oxo moiety (due to the increased iron electrophilicity) than the octahedrally coordinated iron sites in the Grapperhaus example 43…”
Section: Resultsmentioning
confidence: 59%
“…Synthetic model complexes featuring a μ-oxo or μ-hydroxo bridge have been prepared in order to create functional mimics of these enzymes 79. In particular, the interconversion between hydroxo- and oxo-bridged states has been of interest as it is proposed to play an important role during the catalytic cycle of metalloenzymes 10,11. While there are many synthetic examples of diferric Fe–O–Fe units,12–18 few mixed-valent Fe II –O–Fe III complexes and Fe II –O–Fe II complexes have been reported 1922.…”
Section: Introductionmentioning
confidence: 99%
“…We propose that the 2.11-Å shell consists of the three protein-derived ligands as well as a terminal solvent ligand, while the 1.95-Å shell can be reasonably assigned to hydroxo ligands. One of the latter scatterers very likely corresponds to the μ -OH bridge found in hDOHH- R , as analogous bridges in synthetic diferric complexes have Fe III -( μ -OH) distances between 1.94 Å and 2.02 Å [55, 60, 8487]. The other scatterer could, in principle, be assigned to a second hydroxo bridge, but such an Fe III 2 ( μ -OH) 2 core should give rise to an Fe•••Fe distance much shorter than the 3.41-Å separation found for hDOHH- D and hDOHH- D•S .…”
Section: Discussionmentioning
confidence: 99%
“…The 2.15-Å shell likely consists of two histidine ligands and a terminal water ligand based on bond metrics discussed earlier. The 1.98-Å shell would comprise a terminal carboxylate ligand, the hydroxo bridge (1.94 – 2.02 Å) [55, 60, 8587, 97], and the proximal oxygen of a μ -1,2-peroxo ligand (1.86 – 1.94 Å) [52, 7072]. These results compare well to the parameters found by Suzuki and co-workers in the crystal structure of [Fe III 2 ( μ -OH)( μ -1,2-O 2 )(L) 2 ] + (L = bis(6-methylpyridyl-2-methyl)-3-aminopropionate), which has an Fe•••Fe distance of 3.396 Å and average Fe–O and Fe–N distances of 1.95 Å and 2.21 Å, respectively [85].…”
Section: Discussionmentioning
confidence: 99%
“…This method has been previously been used to make a µ-oxo-bridged Fe(III)-salen complex by Webster and co-workers, 60 along with other examples of preparation and application of this complex in the literature. [61][62][63][64][65][66][67][68][69][70][71] However, with the range of salalen, salan and salen ligands (X) [72][73][74][75][76] used in this study, the Fe(X)OAc complex was consistently isolated (Scheme 1). All complexes were recrystallised or washed with cold ethanol and characterised by High-Resolution Mass Spectrometry (HR-MS), elemental analysis and Infra-Red spectroscopy (FT-IR).…”
Section: Complex Synthesismentioning
confidence: 92%